A DSC study of polypropylene chain branching effects on structure formation under rapid cooling and reheating from the amorphous glass. Issue 6 (5th August 2020) - Gloger, Dietrich; Mileva, Daniela; Zhuravlev, Evgeny; Schick, Christoph
Abstract: Isotactic polypropylene, iPP, exists as linear polymer or with side chains, long‐chain branches, LCB. In the melt state, LCBs increase physical interactions between different chains, the entanglements. Under melt deformation, entanglements provide melt strength, a useful property for conversion processes like blow molding or extrusion foaming. LCBs also increase the crystallization temperature of iPP, from about 385 K to above 393 K, comparable to heterogeneous α‐nucleating agents. Here, LCB PP crystallization in fast scanning differential calorimeters was investigated under cooling with rates up to 60, 000 K·s −1 . Results show that LCB PP crystallized via α‐phase up to a cooling rate of 1000 K·s −1, vitrified as amorphous glass at cooling rates above 2000 K·s −1 and hindered mesophase formation upon cooling and via cold crystallization upon heating. This effect increased with branch content and melt elasticity, that is, with chain immobilization in the entanglement network. This melt state enhances α‐nucleation but limits ordering processes at strong undercooling. Results highlight melt structure effects on polymer crystallization, possibly affecting LCB PP processing behavior and product quality. Abstract : Polypropylene is a polymer of worldwide commercial significance, converted into final parts by melt processing and cooling to obtain a solid, crystallized, product. Tools to control product properties, via morphology, are cooling rate and polymer structure. Increasing cooling rates hinder crystallization and eventually supress it, and the amorphous glass forms. Polymer structure influences these structural changes and at which cooling rate they occur. We investigate how a speciality version of polypropylene, with long‐chain branches, LCB, influence crystallization and amorphous glass formation under rapid cooling compared to conventional, linear, polypropylene.